Aquaporins in sepsis- an update - Rump, Katharina; Adamzik, Michael (Frontiers in Immunology, 2024)
Aquaporins (AQPs), membrane proteins that transport water and small solutes, are increasingly recognized for their role in sepsis, particularly in immune modulation, metabolism, and organ protection. Sepsis, marked by an excessive immune response to infection, leads to organ failure and high mortality. Recent research highlights AQPs, especially aquaglyceroporins like AQP3, AQP7, AQP9, and AQP10, as key players in immune cell metabolism, offering new therapeutic possibilities. In sepsis, immune cells shift from oxidative phosphorylation to aerobic glycolysis for faster ATP production, a process aided by AQPs. AQP3, for example, transports glycerol to fuel glycolysis and regulate glucose uptake, while AQP7 influences lipid metabolism and promotes energy production via p38 signaling. Beyond metabolism, AQPs are crucial for immune functions: AQP9 aids neutrophil migration and activation, critical for infection control, while AQP3 modulates inflammation through the TLR4 pathway. AQP1 helps protect against lipopolysaccharide (LPS)-induced kidney injury by promoting macrophage polarization via the PI3K pathway. Therapeutically, AQPs show promise in reducing sepsis-induced organ damage. Inhibiting AQP9 with compounds like HTS13286 or RG100204 decreases inflammation and improves survival by modulating NF-κB signaling. Methazolamide and furosemide, which target AQP5, have reduced lung injury in animal models, showing potential for treating acute lung injury (ALI). Additionally, regulating AQP1 through non-coding RNAs could offer new strategies to mitigate inflammatory responses and organ damage. AQPs also emerge as potential biomarkers for sepsis progression. Altered AQP expression, such as AQP1, AQP3, and AQP5, correlates with sepsis severity, while AQP5 polymorphisms are linked to better outcomes in sepsis-related acute respiratory distress syndrome (ARDS). This suggests AQPs could be used to personalize treatments based on individual profiles. In conclusion, AQPs play a critical role in sepsis, from immune metabolism to inflammation. Targeting AQPs presents novel therapeutic opportunities to improve outcomes and reduce organ damage in sepsis patients.